Proceedings of SPE/IADC Drilling Conference 1993
DOI: 10.2523/25769-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Accounting for the Combined Effect of Drillstring Rotation and Eccentricity on Pressure Losses in Slimhole Drilling

Abstract: Knowledge of the distribution of pressure losses is a key factor to the design of a slimhole well. However, predicting annular pressure losses-the major partis difficult because drillstring motion makes nonnegligible complex contributions that have not been accounted for up to now.Flow in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Harnett and Kostic (1990) reported that the best approach for turbulent flow of power-law fluids in pipes was through the use of the approach of Metzner and Reed graph (1955). The majority of published data and flow predictions of Herschel-Bulkley fluids in concentric and eccentric annuli concern oilwell drilling (Bode et al, 1989;Cartalos and Dupuis, 1993;McCann et al, 1995;Ribeiro and Podio, 1994;Uner et al, 1989;Wang et al, 2000). This reflected the need in the last few decades of a more accurate modeling of annular pressure losses due to an increasing application of new drilling technologies, such as slim hole and coil tubing, characterized by narrower annuli between drill string and borehole or casing walls compared to standard drilling.…”
Section: Introductionmentioning
confidence: 97%
“…Harnett and Kostic (1990) reported that the best approach for turbulent flow of power-law fluids in pipes was through the use of the approach of Metzner and Reed graph (1955). The majority of published data and flow predictions of Herschel-Bulkley fluids in concentric and eccentric annuli concern oilwell drilling (Bode et al, 1989;Cartalos and Dupuis, 1993;McCann et al, 1995;Ribeiro and Podio, 1994;Uner et al, 1989;Wang et al, 2000). This reflected the need in the last few decades of a more accurate modeling of annular pressure losses due to an increasing application of new drilling technologies, such as slim hole and coil tubing, characterized by narrower annuli between drill string and borehole or casing walls compared to standard drilling.…”
Section: Introductionmentioning
confidence: 97%
“…Several researchers investigated the drill string rotation effect on the annulus pressure drop by ascribing to the flow regime (laminar or turbulent), formation of Taylor vortices, drill pipe eccentricity and various other parameters (Ahmed and Miska, 2008;Cartalos and Dupuis, 1993;Erge et al, 2015;Erge et al, 2014;McCann et al, 1995;Ozbayoglu and Sorgun, 2010;Saasen, 2013;Sorgun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Different authors [8][9][10] remarked that concentric annulus models overestimate actual pressure losses in laminar and fully turbulent flow regimes by a percentage of 35-50 depending on the flow parameters. Haciislamoglu and Langlinais 11 presented a model that simulates flow in skewed narrow annular geometries for laminar, transition and turbulent non-Newtonian flow.…”
Section: Literature Reviewmentioning
confidence: 98%